Solve the equation. \( \frac{4}{w^{2}+2 w-8}+\frac{3}{w^{2}+w-6}=\frac{4}{w^{2}+7 w+12} \)
Solución de tutoría real
Responder
Solución
Revisado y aprobado por el equipo de tutoría de UpStudy
The Deep Dive
Let's solve the equation step by step: Given equation: \[ \frac{4}{w^{2}+2w-8} + \frac{3}{w^{2}+w-6} = \frac{4}{w^{2}+7w+12} \] First, we need to factor the denominators: 1. For \(w^{2} + 2w - 8\), we look for two numbers that multiply to \(-8\) and add to \(2\). The factors are \(4\) and \(-2\): \[ w^{2} + 2w - 8 = (w + 4)(w - 2) \] 2. For \(w^{2} + w - 6\), we find factors that multiply to \(-6\) and add to \(1\). The factors are \(3\) and \(-2\): \[ w^{2} + w - 6 = (w + 3)(w - 2) \] 3. For \(w^{2} + 7w + 12\), we look for two numbers that multiply to \(12\) and add to \(7\). The factors are \(3\) and \(4\): \[ w^{2} + 7w + 12 = (w + 3)(w + 4) \] Now rewrite the equation by substituting the factored forms: \[ \frac{4}{(w + 4)(w - 2)} + \frac{3}{(w + 3)(w - 2)} = \frac{4}{(w + 3)(w + 4)} \] Next, find a common denominator, which is \((w + 4)(w - 2)(w + 3)\). Multiply both sides by the common denominator: \[ 4(w + 3) + 3(w + 4) = 4(w - 2) \] Expanding both sides: First, the left side: \[ 4(w + 3) = 4w + 12 \] \[ 3(w + 4) = 3w + 12 \] Therefore, \[ 4w + 12 + 3w + 12 = 7w + 24 \] Now, the right side: \[ 4(w - 2) = 4w - 8 \] Setting the two expanded expressions equal to each other: \[ 7w + 24 = 4w - 8 \] Now, solve for \(w\): Subtract \(4w\) from both sides: \[ 3w + 24 = -8 \] Subtract \(24\) from both sides: \[ 3w = -32 \] Now divide by \(3\): \[ w = -\frac{32}{3} \] Thus, the solution to the equation is: \[ w = -\frac{32}{3} \]